Efficacy and fibrinogen correlations of defibrinogen therapy in idiopathic sudden sensorineural hearing loss - Bing Wang; Wen Zhang; Jin Zhang; Qimei Yang; Bing Han; Hui Liu; Ziyu Zhao (Scientific Reports)
Abstract This study aimed to assess the efficacy of Defibrinogen (DF) therapy in addressing total deafness of idiopathic sudden sensorineural hearing loss (TD-ISSNHL) and investigate the relationship between fibrinogen levels and auditory outcomes. A total of 342 cases of TD-ISSNHL were retrospectively analyzed, with patients divided into two main groups: an experimental group receiving batroxobin in conjunction with Ginaton and glucocorticoids, and a control group receiving Ginaton and glucocorticoids only. Auditory outcomes on the 10th day and the 14th day were analyzed and compared across these groups. Subsequently, the correlation between plasma fibrinogen and prognosis were analyzed within these groups. By the 10th day, the overall efficacy rates in the experimental groups were significantly higher than that in the control group (P = 0.039). Patients extending DF therapy to the 14th day showed a substantial improvement in the overall efficacy rate, from 50.98 to 82.35%. Additionally, significant differences in fibrinogen levels were observed on day 1, day 3, and day 5 ± 1 between the recovery and non-recovery groups (P = 0.013, P = 0.024, P = 0.005). Spearman’s rank correlation analysis indicated weak negative correlations between fibrinogen levels on day 1 and day 3 and hearing improvement, while the level on day 5±1 had a moderate negative correlation. Throughout the follow-up period, no major complications were observed. The study findings suggest that batroxobin therapy not only improves hearing recovery but also maintains plasma fibrinogen at a low and safe level. In addition, sustained low fibrinogen level throughout treatment serves as a predictor for better prognosis in TD-ISSNHL.